Electrocatalytically Active Graphene supported MMo Carbides (MNi, Co) for Oxygen Reduction Reaction. (20th October 2016) - Yang, Huanping; Liu, Jilei; Wang, Jin; Poh, Chee Kok; Zhou, Weijiang; Lin, Jianyi; Shen, Zexiang
Abstract: Graphene-supported NiMo and CoMo carbides with monodisperse feature were prepared and their electrocatalytic activity toward for the ORR was investigated. The NiMo carbide/G and CoMo carbide/G are found to be different in main carbide species (i.e., MoC and Mo2 C, respectively) and in carbide particle size distribution. The ORR tests revealed that CoMo carbide/G exhibit better electrocatalytic performance than NiMo carbide/G in terms of on-set potential, limiting current density and durability. Our present results may open new way for the synthesis of molybdenum carbides, and also suggested that strategies for tuning the molybdenum carbide species within bi-metallic carbides may lead to further enhancements in ORR activity.